Reaping the Benefits of a Transition to Greener Growth in Slovakia - Klein, Caroline (OECD Publishing, 2011)
The transition to a greener economy supported by international environmental commitments and national policies will entail structural changes in consumption patterns and industry structures, resulting in a reallocation of resources in and between countries. Slovakia will need to build an effective framework for green growth to maximise its chances of exploiting cleaner sources of growth and to seize the opportunities to develop new green industries, jobs, and technologies. This requires addressing environmental externalities (for example by extending environmental taxation and removing subsidies) and improving the adaptive capacities of the economy through eco innovation. Reforms to support innovation and R&D spending, such as making existing R&D public support more efficient, strengthening the protection of property rights and developing the venture capital market, are needed. Also, administrative entry barriers in the product market should be reduced, competition in energy markets fostered, and the tertiary education system reformed. This paper relates to the 2010 OECD Economic Review of the Slovak Republic (www.oecd.org/eco/surveys/slovakia)
Keywords: Environment; Economics; Slovak Republic